BEt3‐Initiated Thiol–Ene Click Reactions as a Versatile Tool To Modify Sensitive Substrates1. Issue 36 (13th November 2015) - Gorges, Jan; Kazmaier, Uli
Abstract: BEt3 ‐initiated thiol–ene click reactions are an interesting alternative to the generally used thermal or photochemical thiol additions. The reactions proceed under very mild conditions, and require only 10 mol‐% of BEt3, and an almost stoichiometric amount of thiol. In this regard, this method is an attractive alternative to the other protocols, which often use the thiol component in a large excess. Abstract : BEt3 ‐initiated thiol–ene click reactions proceed under very mild conditions, and require only 10 mol‐% of BEt3 and an almost stoichiometric amount of thiol. The mild reaction conditions allow the modification of substrates containing functionalities that are senstitive to H‐abstraction.